External Environment, Trust and East-West Trade - Thach, Sharon; Marsnik, Susan J.; Lukošius, Vaidotas (Ekonomika, 2005)
A model of trust and commitment in international interfirm alliances in conditions of legal uncertainty/hostility is presented with propositions for testing. Conditions in four Central and East European countries are profiled with respect to varying legal environments and the potential effects of those environments on foreign investment and cooperation.